Accuracy of HC-SR04 Ultrasonic Servo in Servo-Scanned 2D Ranging - Ayunita Haq; Rohim Aminullah Firdaus; Muhimmatul Khoiro; Endah Rahmawati; Nanang Winarto (Universitas Pendidikan Mandalika, 2026)
This study evaluates the measurement accuracy of the HC-SR04 ultrasonic sensor configured as a low-cost two-dimensional servo-scanned ultrasonic ranging system using an Arduino Uno and micro-servo scanning. Unlike prior studies that typically investigate angle, distance, or material effects separately, this work presents an integrated experimental framework that simultaneously examines the combined influence of scanning angle, object distance, and surface characteristics under dynamic scanning conditions. Experiments were conducted at five angles (40°, 75°, 90°, 105°, 150°), four distances (15, 30, 45, and 60 cm), and three materials (brass, wood, plastic), with five repetitions per condition. Performance was assessed using mean absolute error (MAE) and standard deviation. The results show that measurement accuracy varies systematically with scanning geometry. The lowest errors occur near 90°, with average MAE values of approximately 0.5–0.7° for brass, 2–3° for wood, and 4–5° for plastic. At extreme angles (e.g., 150°), errors increase significantly, reaching up to 1.5° (brass), 5° (wood), and >8° (plastic). Across distances, MAE increases from 15 cm to 60 cm, indicating reduced accuracy at longer ranges. Material effects are also pronounced, with brass consistently yielding the lowest error and plastic the highest. These trends are consistent with the expected influence of reflection geometry and signal attenuation, although echo strength was not directly measured. Overall, reliable operation is observed within 75° < θ < 105° and 15–45 cm. These findings provide experimentally grounded insights for improving the performance of a low-cost ultrasonic servo-scanned ultrasonic ranging system in short-range applications.